Long-term (2001–2012) trends of carbonaceous aerosols from a remote island in the western North Pacific: an outflow region of Asian pollutants - S. K. R. Boreddy; M. M. Haque; M. M. Haque; K. Kawamura; K. Kawamura (Atmospheric Chemistry and Physics, 2018)
The present study reports on long-term trends of carbonaceous aerosols in total suspended particulate (TSP) samples collected at Chichijima in the western North Pacific during 2001–2012. Seasonal variations of elemental carbon (EC), organic carbon (OC), and water-soluble organic carbon (WSOC) concentrations showed maxima in winter to spring and minima in summer. These seasonal differences in the concentrations of carbonaceous aerosols were associated with the outflows of polluted air masses from East Asia, which are clearly distinguishable from pristine air masses from the central Pacific. The higher concentrations of carbonaceous aerosols during winter to spring are associated with long-range atmospheric transport of East Asian continental polluted air masses, whereas lower concentrations may be due to pristine air masses from the central Pacific in summer. The annual trends of OC ∕ EC (+0.46 % yr−1), WSOC (+0.18 % yr−1) and WSOC ∕ OC (+0.08 % yr−1) showed significant (p  <  0.05) increases during the period of 2001–2012, suggesting that photochemical formation of WSOC and its contributions to secondary organic aerosols (SOAs) have increased over the western North Pacific via long-range atmospheric transport. We found a significant increase (+0.33 % yr−1) in nss-K+ ∕ EC ratios, demonstrating that concentrations of biomass-burning-derived carbonaceous aerosols have increased, while those of primary fossil-fuel-derived aerosols have decreased over the western North Pacific. Further, secondary biogenic emissions are also important over the western North Pacific as inferred from a significant increase (+0.14 % yr−1) in the concentrations of methanesulfonate (MSA−, a tracer for biogenic sources). This point was further supported by a moderate correlation (r = 0.40) between WSOC and MSA−. We also found a significant increase in OC ∕ TC (total carbon) and WSOC ∕ TC ratios, further suggesting that photochemical formation of WSOC and its contributions to SOAs have increased over the western North Pacific during 2001–2012 via long-range atmospheric transport from East Asia.